2010
DOI: 10.2139/ssrn.1695417
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Giving and Economic Growth: Time Series Evidence for the US

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Higher levels of remittances received, a higher GDP per capita, and improved control of corruption reduce the WGI ranking of a country, that is, increasing the likelihood of a higher percentage of respondents assuming generous attitudes. These findings follow those of Licuanan et al (), Beyene (), Heinemann (), Armellini and Basu (), Persson and Tabellini (), and Borck (). Countries with higher levels of domestic savings and northern countries tend to rank as less generous.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Higher levels of remittances received, a higher GDP per capita, and improved control of corruption reduce the WGI ranking of a country, that is, increasing the likelihood of a higher percentage of respondents assuming generous attitudes. These findings follow those of Licuanan et al (), Beyene (), Heinemann (), Armellini and Basu (), Persson and Tabellini (), and Borck (). Countries with higher levels of domestic savings and northern countries tend to rank as less generous.…”
Section: Resultssupporting
confidence: 91%
“…However, we also expect that the level of personal remittances received (as a percentage of GDP) reduces the magnitude of the WGI for a country, which follows Licuanan et al (), Beyene (), and Akkoyunlu (). Recall that, although we must control for the values of real GDP per capita (Armellini & Basu, ; Heinemann, ) and the level of corruption (Borck, ; Persson & Tabellini, ), we do not have prior expectations regarding the signs of the estimated coefficients for these variables.…”
Section: The Empirical Section—data Results and Their Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Moreover, conducting geographical studies sheds light on the regional dimension of fundraising, the "philanthropy market," and the formative effect of the community context on philanthropic donor behavior (Wolch & Geiger, 1985;Wolpert & Reiner, 1984). Scholars have found that local contexts and geographical disparities set important conditions for regional variations in philanthropy and giving (Bekkers, 2016;Card, Hallock, & Moretti, 2010;Clerkin, Paarlberg, Christensen, Nesbit, & Tschirhart, 2013;Lengauer & Tödtling, 2010;Wolpert, 1988Wolpert, , 1995 at various geographical scales (Bekkers, 2016, p. 124;Havens & Schervish, 2005;Heinemann, 2010;von Schnurbein & Bethmann, 2010). Cross-national comparison reveals the impact of the political, economic, and social and cultural context on philanthropic giving as well as on the size and scope of the not-for-profit sector (Salamon & Anheier, 1998;Wiepking & Handy, 2015, p. 597) 3 .…”
Section: The Philanthropic Fieldmentioning
confidence: 99%